2022
DOI: 10.1186/s12913-022-07744-6
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic barriers and healthcare in China: Chaoshan vs. Mandarin

Abstract: Background China has 129 dialects with Mandarin as the standard and Chaoshan as the major dialect of the Chaoshan region in Guangdong. This study aimed to describe the dialect competence and usage, communication difficulty, impact of linguistic barriers, and subjective experience in healthcare. Methods Healthcare providers (n = 234) and healthcare consumers (n = 483) at two tertiary teaching hospitals in Shantou, Chaoshan region participated in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Patients rated their level of agreement with each CRBS item on a 5-point Likert scale, with response options ranging from 1 (strongly disagree) to 5 (strongly agree). Higher scores indicated greater barriers to CR [ 21 ]. Averages of the CRBS subscales were calculated from the scores on each item included in the subscale.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients rated their level of agreement with each CRBS item on a 5-point Likert scale, with response options ranging from 1 (strongly disagree) to 5 (strongly agree). Higher scores indicated greater barriers to CR [ 21 ]. Averages of the CRBS subscales were calculated from the scores on each item included in the subscale.…”
Section: Methodsmentioning
confidence: 99%
“…The regional dialect is Chaoshan, which is considered one of the most difficult Chinese dialects to learn and is reportedly spoken by more than 70% of the population in the Chaoshan region. A recent cross-sectional study in Shantou reported that linguistic barriers significantly impact health care delivery with perceived adverse impacts on the ability of the entire health care system to operate effectively [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is evident in various communities and a region, including China, that multilingualism (the presence of more than one language) adversely affects health ( 14 ). In this regard, Zhang et al ( 15 ) proposed opting for interventions such as professional interpreter service, service-learning interpreter programs, or mobile interpreting apps that are medically accurate and culturally sensitive for dialectally diverse China.…”
Section: Introductionmentioning
confidence: 99%